Assessment of abdominal obesity using 3D body scanning technology - Suhana Japar,; Thamilvaani Manaharan,; Asma Ahmad Shariff,; Abdul Majid Mohamed,; Amir Feisal Merican Aljunid Merican, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Abdominal obesity is an important contributor for health risk factors such as hypertension, diabetes mellitus and hypercholesterolemia. Therefore, the application of a proper method is important prerequisite in performing abdominal obesity assessment. In this study, we applied 3D body scanning technology to measure waist circumference (WC), hip circumference (HC) and waist to hip ratio (WHR) precisely in an effort to improve the current health assessment for abdominal obesity. A total of 200 Malaysian women with sedentary lifestyle, aged between 18 and 60 years participated in this study. Paired t-test was used to determine the differences between the automated (3D body scanner) and manual measurements of WC, HC and WHR. 3D body scanner measurements show that 27% of subjects had mild abdominal obesity (80 - 90 cm) and 34.5% of subjects had severe abdominal obesity (≥90 cm) based on WC cutoff points. Based on WHR cutoff points, 57% of subjects had abdominal obesity (≥0.85) while the remaining were without abdominal obesity (<0.85). Lower percentages of abdominal obesity prevalence were reported for both WC and WHR categories using manual measurements. We also found that in normal BMI category, 8.5% of subjects have mild abdominal obesity based on automated measurements while only 5.5% of subjects were identified on manual measurements. The result of this study indicated that 3D body scanner provided better assessment method as it enables detection of abdominal obesity in more subjects based on WC and WHR categories. Public agencies are encouraged to consider the application of 3D body scanning in health assessment of abdominal obesity.